Wave-induced residual response and liquefaction of a nonhomogeneous layered seabed - Sui, Titi; Yang, Musheng; Peng, Li; Chen, Jiandong; Zhang, Chi; Zheng, Jinhai (Frontiers in Marine Science, 2024)
Numerical studies were conducted on the wave-induced residual liquefaction of a silt–coarse sand layered seabed. Fully dynamic soil equations and residual seabed response equations were incorporated into the development of a numerical model. The numerical results were compared with theoretical solutions and experimental data from previous studies. Relatively good agreement was found in this comparison, validating the reliability of the proposed numerical model. The present model was applied to systematically investigate the wave-induced residual response with a silt–coarse sand layered seabed. The effects of coverage thickness, permeability, Young’s modulus in the upper silt layer on the residual response of the seabed were carefully examined. Numerical simulations indicate that the potential liquefaction is prone to occur with low permeability of the upper silt layer and shallower water depth, and the effect of coverage thickness of the silt layer on pore pressure and liquefaction potential is determined by shear stress ratio (χ) and effective normalized spreading parameter (Se) which represent the “generation power” and “dissipation potential” for residual pore pressure. The performance of the pore pressure and liquefaction in the layered seabed is the result of a trade-off between two non-dimensional parameters.